CHEMLIT: Development and Feasibility of a Sensor-Based Chemistry Practicum Tool for Electrolyte Solutions - Lorry Enjlina Br Surbakti; Maria Murniyanti Parhusip; Natasya Patulak; Septiany Ch. Palilingan; Stefan Marco Rumengan; Jakub Saddam Akbar (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Chemistry learning requires the integration of macroscopic, submicroscopic, and symbolic representations. However, limited availability of practicum tools in senior high schools often hinders students’ comprehensive understanding of chemical concepts, particularly in electrolyte and nonelectrolyte solutions. This study aimed to develop and implement CHEMLIT, a sensor-based chemistry practicum tool designed to support learning on solution electrical conductivity. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Needs analysis was conducted through classroom observations and teacher interviews, followed by prototype design, assembly, calibration, and functional testing to ensure stability and safety. The implementation involved two senior high schools in the Minahasa region, with chemistry teachers serving as reviewers and students as trial users. Feasibility was evaluated by media experts, material experts, teachers, and students using five-point Likert-scale questionnaires, and the data were analyzed by converting scores into percentage-based feasibility criteria. Product feasibility was evaluated through validation by media experts, subject matter experts, chemistry teachers, and students using questionnaire instruments. The validation results indicated a very high level of feasibility, with scores of 91.7% from media experts, 96% from material experts, 92% from teachers, and student responses exceeding 93.99%, categorized as very good. These findings indicate that CHEMLIT meets technical, visual, and content feasibility standards and can serve as an alternative practicum tool for teaching electrolyte and non-electrolyte solutions, especially in schools with limited laboratory facilities. Its novelty lies in a portable sensor-based design that integrates quantitative conductivity measurement into conventional testing without complex digital systems.